2013
DOI: 10.1155/2013/586561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma Irradiation on Bacterial Microflora Associated with Human Amniotic Membrane

Abstract: Human amniotic membrane is considered a promising allograft material for the treatment of ocular surface reconstruction, burns, and other skin defects. In order to avoid the transmission of any diseases, grafts should be perfectly sterile. Twenty-five amniotic sacs were collected to determine the microbiological quality of human amniotic membrane, to analyze the radiation sensitivity pattern of the microorganism, and to detect the radiation decimal reduction dose (D10) values. All the samples were found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…41 Researchers have shown that UV, X-and γradiation could yield novel bioactive compounds in plants and animal models. [44][45][46] In the present study, after exposure of biosurfactant producers to ultraviolet light at different time intervals, various biochemical results indicated that the organisms were mostly not affected by short-term exposure (0-60 s) to UV light. Since all biochemical tests gave negative results between 600-900 s of isolates exposure to UV rays coupled with confirmatory result by culturing the remains of the isolates on nutrient agar where no growth was recorded, it can be concluded that 600-900 s exposure to UV rays destroyed the isolates completely while different growth and result patterns between 15 s to 300 s of UV rays indicated that the genetic makeup of the isolates were modified leading to various biochemical results recorded.…”
Section: Biochemical Reactions Of Uv-irradiated Pseudomonas Aeruginossupporting
confidence: 44%
“…41 Researchers have shown that UV, X-and γradiation could yield novel bioactive compounds in plants and animal models. [44][45][46] In the present study, after exposure of biosurfactant producers to ultraviolet light at different time intervals, various biochemical results indicated that the organisms were mostly not affected by short-term exposure (0-60 s) to UV light. Since all biochemical tests gave negative results between 600-900 s of isolates exposure to UV rays coupled with confirmatory result by culturing the remains of the isolates on nutrient agar where no growth was recorded, it can be concluded that 600-900 s exposure to UV rays destroyed the isolates completely while different growth and result patterns between 15 s to 300 s of UV rays indicated that the genetic makeup of the isolates were modified leading to various biochemical results recorded.…”
Section: Biochemical Reactions Of Uv-irradiated Pseudomonas Aeruginossupporting
confidence: 44%
“…Amniotic scaffolds have been produced after extensive processing and decellularization techniques to address concerns regarding transmissible diseases in human medicine . Amniotic scaffolds can also be dehydrated, thereby allowing sterilization with gamma irradiation . Such process improves safety, facilitates storage at room temperature, and allows use in a point‐of‐care clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] Amniotic scaffolds can also be dehydrated, thereby allowing sterilization with gamma irradiation. 22,26,27 Such process improves safety, facilitates storage at room temperature, and allows use in a point-of-care clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…The natural floral contamination of fresh AM obtained by ECS in the Queens’s Medical Centre, Nottingham University Hospitals NHS trust, was shown to be considerably lower than literature reported from normal vaginal deliveries 20,24,25 . 40% of the tested AM showed no signs of bioburden contamination, similar to results previously reported (39%) 20 .…”
Section: Discussionmentioning
confidence: 59%